Bio-refining of seaweed: a sustainable source of chemicals and fuel? - Kostas, Emily Tsambika (2017)
The research presented in this thesis evaluated a range of UK native seaweeds as potential feedstocks for both bioethanol and speciality chemical production, with the objective of developing a putative bio-refining process. The gross chemical compositions of nine different UK species of seaweed were determined (Chapter 3) to evaluate their potential for bioethanol production. The carbohydrate contents were within the range 16.8 – 41.8 % (d/w). Three species were selected for further work targeted at bioethanol production. Methodologies involved using thermo-chemical pre-treatments followed by enzymatic hydrolysis. Optimisation experiments concluded that water based (hydrothermal) pre-treatments were most suitable for both D. carnosa and U. lactuca spp (121°C, 24 – 30 min, 15% and 10% (w/v) solids, respectively) to maximise glucose liberation. In contrast dilute acid hydrothermal pre-treatment (1.5 N H2SO4, 121°C, 24 min, 25% (w/v) solids) was most suitable for L. digitata. Feedstocks were produced using optimised conditions for trial fermentations (using S. cerevisiae NCYC2592). These produced yields of 78.4 - 94.5% theoretical ethanol, which equated to 15.4-20.4 kg of pure ethanol per metric tonne of native seaweed. The thermo-chemical pre-treatment of seaweed generated a liquid fraction rich in an array of different monosaccharides inherent to seaweed which was used to identify microorganisms capable of fermenting seaweed monosaccharides into ethanol using a novel phenotypic microarray approach (Chapter 5). Whilst S. cerevisiae spp were suggested to be the most suitable (and efficient) for fermentation of C6 sugars, the yeast stain P. anomala TP12 was able to utilize a mixture of sugars inherent to seaweed. Attempts were made to link both bioethanol production and fucoidan extraction as part of a novel bio-process using L. digitata (Chapter 6). At pilot plant scale, fucoidan was extracted with a purity of 65% and an overall extraction efficiency of 17% was attained. Pre-treatment and enzymatic hydrolysis of the remaining waste residue generated a feedstock that achieved 93.8% theoretical glucose, which when fermented yielded 94.4% of theoretical ethanol. Furthermore, extracts from waste streams of the putative process exhibited both antioxidant and antimicrobial activities.